INTEGRASI SISTEM POLITIK ISLAM DALAM KANCAH PERPOLITIKAN NASIONAL INDONESIA - Mugiyono, Mugiyono (JIA (Jurnal Ilmu Agama), 2015)
The Majority of Muslims in Indonesia are very influential in politics and state government activities. From the beginnings of Islam in Indonesia, Muslims play an important role in political life and state. It is characterized by the many Islamic kingdoms that once lived in this country. Many Muslim fighters which are known or unknown in the public have been fighting for independence and defending it from the invaders. Many of muslims politicians participate in the implementation of important political policies. Thus this state lasts from the beginning of Islam to Indonesia's independence until now. The perpetrators pioneering history of independence and the founder of the state of Indonesia are predominantly Muslim. They incorporate the essence of Islam into the foundations of the state. Vertices of Islam among the Muqadimah or the Preamble of the Constitution of 1945, which consisted of four paragraphs, the formulation of Pancasila is the basis of the Republic of Indonesia, terms and forms of government agencies, such as the DPR (House of Representatives), MPR (Consultative Assembly People), MA (Supreme Court) and others. That is, the Islamic political system born of Muslim thinkers and based al-Qur'an and Sunnah has given many colors and patterns for the form and system of Indonesian politics. This needs to be proven scientifically through research.